Social entrepreneurship, co‐production, and post‐disaster recovery - Rayamajhee, Veeshan; Storr, Virgil Henry; Bohara, Alok K. (Disasters, 2022)
Post‐disaster recovery requires co‐production; that is, the inputs of citizens are essential for successful community recovery to occur. Citizens contribute to post‐disaster recovery by volunteering, taking on consultative and decision‐making roles within their communities, and directly participating in post‐disaster reconstruction efforts. Without meaning ful contributions from citizens—the intended beneficiaries—unilateral efforts by public officials and authorities will inevitably fail. This study shows that social entrepreneurs can thus play a critical role in spurring post‐disaster recovery by facilitating co‐production. It focuses on the role of social entrepreneurs after disasters and centres on one rural village, Giranchaur Namuna Basti in the Sindhupalchowk District of Nepal. Specifically, the study uses the case of the Dhurmus Suntali Foundation's Namuna village project in Giranchaur following the 7.8‐magnitude earthquake that struck on 25 April 2015 to examine the pivotal role that social entrepreneurs assume in promoting voluntary activities, community engagement, and participation in post‐disaster recovery efforts. الملخص يتطلب التعافي من الكوارث إنتاجًا مشتركًا حيث إن مدخلات المواطنين ضرورية لحدوث تعافي مجتمعي ناجح. يساهم المواطنون في التعافي من الكوارث بالتطوع، والاضطلاع بأدوار استشارية وصنع القرار داخل مجتمعاتهم، والمشاركة المباشرة في جهود إعادة الإعمار بعد الكوارث. بدون مساهمات ذات مغزى من المواطنين ‐ المستفيدين والمستهدفين ‐ ستفشل حتمًا الجهود أحادية الجانب من المسؤولين والسلطات العامة. تُظهر هذه الدراسة أن رواد الأعمال الاجتماعيين يمكنهم بالتالي أن يؤدوا دورًا حاسمًا في تحفيز التعافي بعد الكوارث بتسهيل الإنتاج المشترك. نحن نركز على دور رواد الأعمال الاجتماعيين بعد الكوارث ونتركز حول قرية ريفية واحدة هي غيرانشار نامونا باستي (GCNB) في مقاطعة سينهوباتشوك في نيبال. على وجه التحديد، نستخدم حالة مشروع قرية نامونا التابع لمؤسسة Dhurmus Suntali في Giranchaur في أعقاب الزلزال الذي بلغت قوته 7.8 درجة في عام 2015 كمنشأة شبه تجريبية لفحص الدور المحوري الذي يلعبه رواد الأعمال الاجتماعين في تعزيز الأنشطة التطوعية والمشاركة المجتمعية والمشاركة في مرحلة ما في جهود التعافي ما بعد الكوارث. 摘要 灾后恢复需要合作 即公民的投入对于成功的社区恢复是至关重要的。公民通过提供志愿服务 在社区内承担咨询和决策角色以及直接参与灾后重建努力 为灾后恢复作出贡献。如果公民（预期受益者）没有作出有意义的贡献 政府官员和当局的单方面努力将不可避免地失败。这项研究表明 社会企业家可以通过促进合作生产 在促进灾后恢复方面发挥关键作用。我们关注灾后社会企业家的作用 并以尼泊尔辛杜帕尔乔克区一个名为Giranchaur Namuna Basti （GCNB）的村庄为中心。具体来说 我们以2015年7.8级地震后达尔穆斯·桑塔利基金会在吉兰乔尔的纳穆纳村项目为例 建立了一个准实验 以检验社会企业家在促进志愿活动、社区参与和灾后恢复努力中发挥的关键作用。